2007
DOI: 10.1093/ecam/nem125
|View full text |Cite
|
Sign up to set email alerts
|

Crocus sativus L. (Saffron) Extract and its Active Constituents (Crocin and Safranal) on Ischemia‐Reperfusion in Rat Skeletal Muscle

Abstract: Saffron and its constituents have been shown to decrease ischemia-reperfusion (I/R) injury in kidney or brain tissues. In this study, the effects of saffron ethanolic extract and its constituents, crocin and safranal, were evaluated in skeletal muscle during I/R injury. Hind limb ischemia was induced using clamping the common femoral artery and vein. After 2 h ischemia, the clamp of the femoral vessels of animals was taken off and the animal underwent 1h reperfusion. Muscle injuries were evaluated by recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 39 publications
4
91
0
1
Order By: Relevance
“…Reduction of lipid peroxidation, improving of total antioxidant capacity, total thiol contents, and GSH pool, as well as antioxidant enzyme activities such as superoxide dismutase, catalase, and GSH-related enzymes were reported for saffron, crocin, and safranal following ischemia-reperfusion injury Saleem et al, 2006;Hosseinzadeh et al, 2008;Zheng et al, 2007). The modifying effects of saffron and its carotenoids on antioxidant enzymatic activities have also been shown in other experimental models (Premkumar et al, 2001;Premkumar et al, 2003;Shen and Qian, 2006).…”
Section: Effect Of Saffron and Crocin On Mms-induced Dna Damagementioning
confidence: 84%
See 1 more Smart Citation
“…Reduction of lipid peroxidation, improving of total antioxidant capacity, total thiol contents, and GSH pool, as well as antioxidant enzyme activities such as superoxide dismutase, catalase, and GSH-related enzymes were reported for saffron, crocin, and safranal following ischemia-reperfusion injury Saleem et al, 2006;Hosseinzadeh et al, 2008;Zheng et al, 2007). The modifying effects of saffron and its carotenoids on antioxidant enzymatic activities have also been shown in other experimental models (Premkumar et al, 2001;Premkumar et al, 2003;Shen and Qian, 2006).…”
Section: Effect Of Saffron and Crocin On Mms-induced Dna Damagementioning
confidence: 84%
“…Saffron is used in folk medicine as an anodyne, antidepressant, sedative, respiratory decongestant, anticatarrhal, expectorant, antispasmodic, eupeptic, stomachic, carminative, diaphoretic, gingival sedative, aphrodisiac, and emmenagogue (Rios et al, 1996;Abdullaev and Espinosa-Aguirre, 2004). Further, modern pharmacological studies have shown that saffron extract or its active constituents have learning-and memoryimproving properties (Abe and Saito, 2000;Pitsikas et al, 2007), anticonvulsant (Hosseinzadeh and Khosravan, 2002;Hosseinzadeh and Talebzadeh, 2005), antidepressant (Hosseinzadeh et al, 2004;Akhondzadeh et al, 2004), antiinflammatory (Hosseinzadeh and Younesi, 2002), antiischemic Hosseinzadeh et al, 2008;Zheng et al, 2007), and antitumor effects (Abdullaev, 1993(Abdullaev, , 2002Abdullaev and Espinosa-Aguirre, 2004). Radical scavenging, antioxidant activity, and promotion of the diffusivity of oxygen in different tissues were also reported for saffron extract or its bioactive constituents (Rios et al, 1996;Verma and Bordia, 1998;Assimopoulou et al, 2005;Kanakis et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…The cardioprotective effect of saffron and one of its constituents, crocin, in a stressful condition following the injection of high dose of isoproterenol has been confirmed in recent studies (Goyal et al, 2010;Joukar et al, 2010;Sachdeva et al, 2010). In addition, the attenuation effect of saffron on ischemicreperfusion injury of skeletal muscle (Hosseinzadeh et al, 2009), kidney (Hosseinzadeh et al, 2005) and ischemic brain tissue injury (Vakili et al, 2011) is reported. The effect of saffron on electrophysiological aspects such as slowing the electrical conductivity of the heart, long QT interval (Joukar, 2012) and increasing the Wenckebach block cycle length and nodal functional refractory period in vitro (Khori et al, 2011), was also documented.…”
Section: Introductionmentioning
confidence: 86%
“…Saffron's extract effect on declining blood pressure and its loosening influences on smooth muscles on rats and guinea pigs has been examined (Fatehi et al, 2003). Researchers have demonstrated that saffron's extract reduces ischemia and blood reestablishment in kidney and skeleton muscles (Hosseinzadeh et al, 2009;Hosseinzadeh and Younesi, 2022). Saffron's potential anti arrhythmias role has been reported in curing supraventricular tachycardia arrhythmias.…”
Section: Introductionmentioning
confidence: 99%